Pendekatan Business Model Canvas dan SWOT Analysis dalam Pengembangan Usaha pada Coffee Shop White Dove (Jurnal Ekonomi dan Bisnis Islam, 2025)
AbstractThis research aims to identify and analyze the form of the business model used at the White Dove Coffee Shop in developing the business using the Business Model Canvas (BMC) approach and to determine the business development strategy used at the White Dove Coffee Shop through SWOT analysis in each element of the Business Model Canvas (BMC). Data collection methods were carried out using observation, interviews, and documentation. The data analysis techniques used in this research are data reduction, display, and verification. The results of this research are that the White Dove coffee shop applies the Business Model Canvas (BMC) through strategic partnerships with suppliers, online and offline sales activities, and quality resource management. The main values offered include product variety, a comfortable atmosphere, and long operating hours. White Dove maintains customer relationships through product innovation and promotions, with a focus on the student, student, and working segments. SWOT analysis identifies strengths such as quality products and weaknesses in HR distribution. Opportunities for menu expansion and franchise partnerships, as well as threats of competition, are important factors in business development strategies.Keywords: Business Model Canvas (BMC); SWOT. AbstrakPenelitian ini bertujuan mengidentifikasi dan menganalisis bentuk dari gambaran model usaha yang digunakan coffee shop White Dove dalam mengembangkan usaha dengan menggunakan pendekatan Business Model Canvas (BMC) dan untuk mengetahui strategi pengembangan usaha yang digunakan pada coffee shop White Dove melalui analysis SWOT pada setiap elemen Business Model Canvas (BMC). Metode pengumpulan data dilakukan dengan cara observasi, wawancara, dan dokumentasi. Adapun teknis analisis data yang digunakan dalam penelitian ini adalah data reduction, data display, dan verifikasi. Hasil penelitian ini berupa coffee shop White Dove menerapkan Business Model Canvas (BMC) berupa kemitraan strategis dengan supplier, aktivitas penjualan online dan offline, serta pengelolaan sumber daya berkualitas. Nilai utama yang ditawarkan meliputi variasi produk, suasana nyaman, dan jam operasional yang panjang. White Dove menjaga hubungan pelanggan melalui inovasi produk dan promosi, dengan fokus pada segmen pelajar, mahasiswa, dan pekerja. Analisis SWOT mengidentifikasi kekuatan seperti produk berkualitas dan kelemahan pada distribusi SDM. Peluang ekspansi menu dan kemitraan franchise serta ancaman persaingan, menjadi faktor penting untuk strategi pengembangan bisnis.Kata Kunci: Business Model Canvas (BMC); SWOT.